How to Start a Food Business: Writing a Business Plan - Soohyoun Ahn; Lisa House; Renée Goodrich-Schneider (EDIS)
Before starting a new food business, you should set a goal and have detailed plans to accomplish that goal. But writing a good business plan is often a challenge and it requires a great amount of effort. This 4-page fact sheet provides guidance on how to write a good food-business plan. Written by Soohyoun Ahn, Lisa House, and Renée Goodrich-Schneider, and published by the UF Department of Food Science and Human Nutrition, December 2014. (Photo: iStock/Thinkstock)